Protein Expression in Mammalian Cells Methods and Protocols - Hartley, James L.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2012)
Through all of the recent progress provided by high throughput DNA sequencing technologies, it has become clearer and clearer that the study of proteins and protein organelles will be the key to unlocking our ability to manipulate cells and intervene in human disease.  In Protein Expression in Mammalian Cells: Methods and Protocols, expert researchers in the field present a compendium of vital techniques to further our knowledge of mammalian protein expression.  Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips for troubleshooting and avoiding known pitfalls.   Authoritative and concise, Protein Expression in Mammalian Cells: Methods and Protocols will aid scientists seeking to delve deeper into our own biology through the medium of other mammalian cells and proteins.
Why Proteins in Mammalian Cells? -- Large Scale Transfection of Mammalian Cells -- Selection of High Expressing Mammalian Cells by Surface Display of Reporters -- Expression of a Secreted Protein in Mammalian Cells Using Baculovirus Particles -- Transfection of Difficult-to-Transfect Primary Mammalian Cells -- Stable Protein Expression in Mammalian Cells Using Baculoviruses -- Using Matrix Attachment Regions to Improve Recombinant Protein Production -- Controlling Apoptosis to Optimize Yields of Proteins from Mammalian Cells -- Post-Transcriptional Regulatory Elements for Enhancing Transient Gene Expression Levels in Mammalian Cells -- Converting Monoclonal Antibodies into Fab Fragments for Transient Expression in Mammalian Cells -- Generation of High-Expressing Cells by Methotrexate Amplification of Destabilized Dihydrofolate Reductase Selection Marker -- Tools for Co-Producing Multiple Proteins in Mammalian Cells -- Identification and Characterization of Protein Glycosylation Using Specific Endo- and Exoglycosidases -- Strategies for the Efficient Transfection of CHO-Cells with Plasmid DNA -- Methods for Constructing Clones for Protein Expression in Mammalian Cells -- Optimizing Transient Recombinant Protein Expression in Mammalian Cells.
Keywords: Proteins .; Protein Science